Effects of perennial wildflower strips and landscape structure on birds in intensively farmed agricultural landscapes - Schmidt, Annika; Fartmann, Thomas; Kiehl, Kathrin; Kirmer, Anita; Tischew, Sabine (Basic and applied ecology, 2022)
Farmland bird populations are in a deep crisis across Europe. Agri-environment schemes (AES) were implemented by the European Union to stop and reverse the general decline of biodiversity in agricultural landscapes. In Germany, flower strips are one of the most common AES. Establishing high-quality perennial wildflower strips (WFS) with species-rich native forb mixtures from regional seed propagation is a recent approach, for which the effectiveness for birds has not yet been sufficiently studied. We surveyed breeding birds and vegetation on 40 arable fields with WFS (20 with single and 20 with aggregated WFS) and 20 arable fields lacking WFS as controls across Saxony-Anhalt (Germany). Additionally, vegetation composition, WFS quantity and landscape structure (e.g. distance to nearest woody element) were considered in our analyses. All WFS were established with species-rich native seed mixtures (30 forbs) in agricultural practice as AES. Arable fields with WFS had a higher species richness and territory density of birds than controls, confirming the effectiveness of this AES. A forb-rich vegetation was the main driver promoting birds. Flower strip quantity at the landscape level had positive effects only on bird densities, but also single WFS achieved benefits. A short distance from WFS to woody elements increased total bird species richness. However, the density of farmland birds, which are target species of these AES, were negatively affected by the proximity and proportion of woody elements in the vicinity. The effect of the proportion of non-intensively used open habitats and overall habitat richness was unexpectedly low in the otherwise intensively farmed landscape. Species-rich perennial WFS significantly promoted breeding birds. Successful establishment of WFS, resulting in high-quality habitats, a high flower strip quantity as well as implementation in open landscapes were shown to maximise the effectiveness for restoring declining and AES target farmland birds. [Display omitted]